2019
DOI: 10.3390/ijms20092266
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels Involved in Tooth Pain

Abstract: The tooth has an unusual sensory system that converts external stimuli predominantly into pain, yet its sensory afferents in teeth demonstrate cytochemical properties of non-nociceptive neurons. This review summarizes the recent knowledge underlying this paradoxical nociception, with a focus on the ion channels involved in tooth pain. The expression of temperature-sensitive ion channels has been extensively investigated because thermal stimulation often evokes tooth pain. However, temperature-sensitive ion cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 174 publications
(252 reference statements)
1
28
0
7
Order By: Relevance
“…administration of the TLR4 antagonist and for western blotting analysis. Our novel findings suggesting that TLR4 receptor processes in the rat caudal medulla may mediate nociceptive responses evoked by the TRPA1 agonist MO, which is a welldocumented inflammatory irritant (Woolf and Wall, 1986;Hu et al, 1993;Yu et al, 1994;Cairns et al, 1998;Chiang et al, 1998), are consistent with previous studies documenting the presence of TRPA1 in the tooth pulp (Hargreaves and Ruparel, 2016;Lee et al, 2019) and the involvement of TLR4 and TRPA1 processes in several other pain models (Kobayashi et al, 2005;Christianson et al, 2011;Ohara et al, 2013;Fischer et al, 2014;Tramullas et al, 2014;Sun et al, 2015;Bruno et al, 2018). Some of these studies have included investigations showing that TLR4 antagonists such as LPS-RS can attenuate nociceptive processes (Christianson et al, 2011;Sun et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…administration of the TLR4 antagonist and for western blotting analysis. Our novel findings suggesting that TLR4 receptor processes in the rat caudal medulla may mediate nociceptive responses evoked by the TRPA1 agonist MO, which is a welldocumented inflammatory irritant (Woolf and Wall, 1986;Hu et al, 1993;Yu et al, 1994;Cairns et al, 1998;Chiang et al, 1998), are consistent with previous studies documenting the presence of TRPA1 in the tooth pulp (Hargreaves and Ruparel, 2016;Lee et al, 2019) and the involvement of TLR4 and TRPA1 processes in several other pain models (Kobayashi et al, 2005;Christianson et al, 2011;Ohara et al, 2013;Fischer et al, 2014;Tramullas et al, 2014;Sun et al, 2015;Bruno et al, 2018). Some of these studies have included investigations showing that TLR4 antagonists such as LPS-RS can attenuate nociceptive processes (Christianson et al, 2011;Sun et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…LPS from gramnegative bacteria is the main exogenous TRL4 agonist during infection-associated dental pain and likely sensitizes the transient receptor potential vanilloid 1 (TRPV1) via TRL4 activation in the trigeminal sensory neurons (Diogenes et al, 2011;Green et al, 2016). There is also evidence that TRPV1 is co-expressed with TRPA1 in many sensory neurons, including those in tooth pulp, associated with small-diameter C-fibers in the trigeminal ganglion as well as in the dorsal root ganglion (Kobayashi et al, 2005;Sadofsky et al, 2014;Hargreaves and Ruparel, 2016;Gouin et al, 2017;Lee et al, 2019). This co-expression might lead to functional interactions between these two subtypes of TRP receptors (Fischer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of TRP channels has been suggested to be involved in mammalian mechanosensation under normal physiological conditions as well as in pathophysiology (2,(4)(5)(6). Among the suggested TRP channels, there is substantial evidence of TRPA1 being involved in mechanical sensory stimulation, and especially in noxious mechanotransduction e.g., related to nerve-injury, inflammation and anti-cancer treatment (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…They are activated by a variety of stimuli and are involved in the generation and signal transduction of acute nociceptive and pathological pain. The number that have been discovered have rapidly increased over the last decade and those that have been studied most extensively are: 1) thermosensitive channels, including the heatsensing channels transient receptor potential vanilloid (TRPV)1 (>43°C), TRPV2 (-52°C), TRPV4 (27-35°C), and transient receptor potential melas-tatin (TRPM)3 (>40°C) and the cold-sensing channels TRPM8 (<26°C) and transient receptor potential ankyrin 1 (TRPA1) (<17°C); 2) mechanosensitive channels, including TRPV1, TRPV2, TRPV4, TRPM3, TRPA1, epithelial sodium channel (ENaC), acid-sensing ion channel 3(ASIC3), and Piezo-type mechanosensitive ion channel component 2 (PIEZO2); 3) other channels, including the ATP-binding purinergic receptors P2X2 and P2X3, and the hyperpolarization-activated cyclic nucleotide-gated channels HCN [5].…”
Section: Expression and Distribution Of Receptors And Ion Channels Inmentioning
confidence: 99%
“…Elucidation of the types and properties of nerve fibers innervating dental pulp and of the sensory receptors and ion channels expressed in each type of pulpal nerve fiber is crucial for understanding the peripheral mechanisms of dental pain. Recently, many studies have reported expressions of glutamate receptors and various molecules involved in the release of glutamate in pulpal axons [4,5] and their upregulation in inflamed pulp [6,7]. This suggests that glutamate signaling, associated with the pulpal nerve may play a crucial role in acute and pathologic dental pain.…”
Section: Introductionmentioning
confidence: 99%